Airport Service Quality and Word of Mouth - Adi Nugroho (Institut Transportasi dan Logistik Trisakti, 2022)
The study is about the implementation of airport service quality perception and its relation to Word of Mouth (WOM). The main purpose of the study is to develop an understanding of the airport service quality perception developed by Airport Council International. Furthermore, it investigates the relationship between service quality and WOM and analyzes whether the passengers discuss the airport service quality to other passengers; share the airport experience to social media; and recommend the airport to others or not. These raise the questions whether the service quality could affect Word of Mouth (WOM) including the interaction between variables. The results of the study show that the airport service quality has positive impact toward Word of Mouth and some findings related to the problems.